Chaperone-mediated autophagy protects against retinal photoreceptor degeneration by modulating proteostasis of glucose metabolism enzymes - Raquel Gómez-Sintes; Inmaculada Tasset; Ignacio Ramírez-Pardo; Adrián Martín-Segura; Sandra Alonso-Gil; Antonio Díaz; Kristen Lindenau; Concepción Lillo; Pedro de la Villa; Simone Sidoli; Evripidis Gavathiotis; Ana María Cuervo; et al. (Proceedings of the National Academy of Sciences, 2026)
Defective proteostasis is a hallmark of aging cells and tissues. Among the different components of the proteostasis network, in this study, we focus on a selective form of autophagy known as chaperone-mediated autophagy (CMA), and we set out to understand its physiological role in the retina. Using mice deficient for CMA [knockout for lysosome-associated membrane protein type 2A ( Lamp2A )], we have found that CMA blockade leads to impaired visual function, altered retinal proteostasis, and photoreceptor cell death. Conversely, mice that overexpress human LAMP2A show higher resistance to chemically induced photoreceptor degeneration and slower visual function decline. We found a similar protective effect against retinal degeneration upon pharmacological activation of CMA. To start elucidating the mechanisms behind CMA’s protective role in the retina, we used comparative proteomics and found elevated levels of enzymes related with glucose metabolism in CMA-deficient retinas that phenocopy those observed in old mice retinas. Overall, our results highlight a cytoprotective role for CMA in retina, in part through proteostatic regulation of enzymes involved in glucose metabolism, and support the feasibility of pharmacologically upregulating CMA against retinal degeneration.